Case Report: Primary endodermal sinus tumor on the abdominal wall near the right liver: a diagnostic pitfall - Chen, Shuo; Chen, Feng; Xu, Xiao (Frontiers in Oncology, 2023)
Background Endodermal sinus tumors are rare, especially extragonadal endodermal sinus tumors, which often occur in the midline of the brain, neck, chest, and abdomen. Case summary We present the case of a 37-year-old woman with a mass on the right edge of the liver. Color Doppler ultrasound, computed tomography, and magnetic resonance imaging examinations were performed before the operation. Given these results and the elevation of alpha-fetoprotein, the diagnosis of hepatocellular carcinoma was made. Postoperative pathological examination indicated an endodermal sinus tumor on the abdominal wall near the right liver. The causes of misdiagnosis were analyzed, and the related literature was reviewed. Conclusion Primary endodermal sinus tumors on the abdominal wall near the right liver are easily misdiagnosed as hepatocellular carcinoma due to liver compression and elevated alpha-fetoprotein. The key point of differentiation is the wide basal connection between the tumor and the abdominal wall near the liver. In addition, the enhancement mode of endodermal sinus tumors is different from the enhancement pattern of hepatocellular carcinoma. Core tip Extragonadal endodermal sinus tumors often occur in the midline of the body. Here, we present a case of a primary endodermal sinus tumor on the abdominal wall near the right liver for the first time.